The Combination Truck Routing Problem: A Survey. (2016) - Li, Hongqi; Lv, Tan; Lu, Yingrong
Abstract: The combination-vehicle attributes of vehicle routing problems are additional characteristics that aim to consider more effectively the specificities of real logistics applications. Because various combination truck situations exist, the combination truck routing problem (CTRP) is supported by well-developed literature, especially with respect to the truck and trailer routing problem (TTRP), the rollon-rolloff vehicle routing problem (RRVRP), the tractor and semitrailer routing problem (TSRP), and a variety of heuristics. This article first reviews the three primary forms of the CTRP, providing a survey of problem foundations and heuristics for the TTRP, the RRVRP and the TSRP. Next, this report takes a closer look at comparing the three forms of the CTRP. The TTRP aims to efficiently apply trailers that can attach/detach trucks easily to serve less-than-truckload shipping, and the RRVRP and the TSRP aim to attain high use rates for tractors in different full truckload shipping practices. The three forms of the CTRP share a number of common features. In particular, most of the formulations and heuristic strategies developed for specific problems share many similar characteristics. The CTRP is an extremely rich and promising operations research field. More general formulations and more general-purpose solvers are necessary to address practical combination truck routing applications efficiently and in a timely manner.